NCOA4 and ferritinophagy in hematological malignancies: a double-edged regulator of iron metabolism and cell fate - Chabane, T.; Bouscary, D.; Grignano, E. (Frontiers in Oncology, 2026)
Ferritinophagy, a selective autophagic process mediated by NCOA4, plays a central role in cellular iron homeostasis by mobilizing iron from ferritin to sustain mitochondrial metabolism and redox balance. In cancer, ferritinophagy’s effects vary with context: it can support metabolic fitness in some settings while promoting ferroptotic vulnerability in others. In acute myeloid leukemia (AML), evidence suggests that leukemic stem cells rely more heavily on iron-driven mitochondrial metabolism, making ferritinophagy a potential therapeutic target. This review summarizes current knowledge of NCOA4 regulation and ferritinophagy, discusses their relevance in hematologic malignancies, and highlights therapeutic opportunities and unresolved questions in AML.